Study on e-Commerce in Croatia: Customers’ Preferences (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Rapid development and growth of Internet facilitate business and transforms today’s economies. Nowadays is almost impossible to do business or some other activities without Internet usage. Internet enables transactions among clients and stores, which has positive impact on doing business. E-commerce enhances sales and customers’ shopping experience and improves business processes. This paper aims to present and analyze e-commerce usage in Croatia. Empirical research on e-commerce in Croatia was conducted to investigate clients’ perception and attitudes toward online shopping. Research results revealed that Croats use e-commerce stores, although they named several difficulties, which influence on their online shopping decisions.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.